THE MAKING OF RELIGIOUS MINORITIES IN POST-REFORM INDONESIA: THE FOUR KEYWORDS OF MULTI-ACTOR AUTHORITY DISCOURSE - Rahmat Saehu; Ubaidillah; Muhammad Nur Prabowo Setyabudi; Hidayatullah Rabbani; Ahalla Tsauro (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2026)
Post-Reform Indonesia has witnessed intensified religious contestation in which language plays a central role in defining religious legitimacy, authority, and social belonging. This article examines how four influential labels, namely liberal, deviant (sesat), infidel (kafir), and radical, operate as discursive instruments in the construction of religious minorities. Employing a qualitative approach and Critical Discourse Analysis (CDA), the study analyzes religious fatwas, statements of Islamic organizations, mass media reports, social media content, digital archives, and academic literature produced and circulated between 1998 and 2024. The analysis involved identifying, categorizing, and interpreting discursive patterns related to the production, circulation, legitimization, and contestation of these four keywords across religious, political, and media arenas. The findings demonstrate that these labels function as mechanisms of authority through which state institutions, religious organizations, media actors, and digital publics define orthodoxy, delegitimize opponents, mobilize public sentiment, and reinforce boundaries between majority and minority groups. The study further reveals that digital mediation and electoral competition have expanded the influence of these terms beyond theological debates into broader political and civic domains. At the same time, counter-discourses promoted by the state and major Islamic organizations, including Nahdlatul Ulama and Muhammadiyah, have sought to redefine these labels through narratives of dialogue, citizenship, and religious moderation. This article contributes to the study of religion and power by demonstrating how minority formation is shaped through multi-actor authority discourse. It concludes that linguistic contestation constitutes a crucial arena in the production of religious minorities and the ongoing negotiation of socio-religious harmony in contemporary Indonesia. Abstrak Indonesia pasca-Reformasi ditandai oleh meningkatnya kontestasi keagamaan yang menjadikan bahasa sebagai instrumen penting dalam menentukan legitimasi, otoritas, dan identitas keberagamaan. Artikel ini menganalisis bagaimana empat label yang berpengaruh dalam wacana keagamaan, yaitu liberal, sesat, kafir, dan radikal, berfungsi sebagai perangkat diskursif dalam pembentukan kelompok minoritas keagamaan. Penelitian ini menggunakan pendekatan kualitatif dengan Analisis Wacana Kritis (AWK) terhadap fatwa keagamaan, pernyataan organisasi Islam, pemberitaan media massa, konten media sosial, arsip digital, serta literatur akademik yang diproduksi dan beredar sepanjang periode 1998–2024. Analisis dilakukan melalui proses identifikasi, kategorisasi, dan interpretasi pola-pola wacana yang berkaitan dengan produksi, sirkulasi, legitimasi, dan kontestasi keempat kata kunci tersebut dalam arena keagamaan, politik, dan media. Hasil penelitian menunjukkan bahwa label liberal, sesat, kafir, dan radikal berfungsi sebagai mekanisme otoritas yang digunakan oleh institusi negara, organisasi keagamaan, media, dan publik digital untuk mendefinisikan ortodoksi, mendelegitimasi pihak lain, memobilisasi sentimen publik, serta mempertegas batas antara kelompok mayoritas dan minoritas. Penelitian ini juga menemukan bahwa mediatiasi digital dan kontestasi elektoral memperluas pengaruh label-label tersebut melampaui perdebatan teologis ke ranah politik dan kewargaan. Pada saat yang sama, muncul berbagai narasi tandingan yang dikembangkan oleh negara dan organisasi keagamaan besar seperti Nahdlatul Ulama dan Muhammadiyah melalui wacana dialog, kewargaan, dan moderasi beragama. Artikel ini berkontribusi pada kajian agama dan kekuasaan dengan menunjukkan bahwa pembentukan minoritas keagamaan berlangsung melalui wacana otoritas yang diproduksi oleh berbagai aktor. Studi ini menyimpulkan bahwa kontestasi bahasa merupakan arena penting dalam pembentukan minoritas serta negosiasi harmoni sosial-keagamaan di Indonesia kontemporer.